INFLUENCE OF SINTERING TEMPERATURE ON STRUCTURAL PROPERTIES OF HEMATITE (Fe2O3) NANOPARTICLES AND ITS APPLICATION FOR ELECTROMAGNETIC INTERFERENCE SHIELDING - Chiromawa, Idris Muhammad; Garba Shitu, Ibrahim; Muhammad, Aminu; Kayode Katibi, Kamil; Garba Dirmin Iya, Sani (FUDMA Journal of Sciences, 2024)
Hematite (Fe2O3) nanoparticles have garnered significant attention due to their exceptional magnetic properties and potential applications in advanced technologies, including electromagnetic interference (EMI) shielding. Optimizing these properties through controlled synthesis methods is essential for enhancing their performance in such applications. This study explores the impact of sintering temperature on the structural, magnetic, and EMI shielding properties of hematite nanoparticles synthesized via an auto-combustion method. It was found that increasing sintering temperatures led to a consistent growth in crystallite size, as confirmed by multiple X-ray diffraction (XRD) techniques, including Scherrer's method, the Williamson-Hall methods (UDM, USDM, UDEDM), the Monshi-Scherer Method (MSM), the Size-Strain Plot (SSP) method, the Halder-Wagner method (HWM), and further validated by Field Emission Scanning Electron Microscopy (FESEM) analysis. The nanoparticles exhibited superparamagnetic behaviour with a saturation magnetization (Ms) of 4.0 emu/g, making them particularly advantageous for EMI shielding applications. Furthermore, Fe2O3 nanoparticles were embedded into a polyvinyl alcohol (PVA) matrix to fabricate nanocomposite films, which demonstrated significant improvements in EMI shielding effectiveness. The reflection and absorption losses were enhanced with increasing Fe2O3 content, indicating the nanocomposites' strong capability to attenuate electromagnetic waves. This study underscores the critical role of sintering temperature in optimizing the structural and magnetic properties of hematite nanoparticles, making them highly suitable for advanced technological applications, especially in electromagnetic interference shielding.
Keywords: Hematite (Fe2O3); Nanoparticle; Sintering Temperature; Electromagnetic Interference (EMI) Shielding; Auto-Combustion; Crystallite Size